Semantics Meaning Lyric in You Are The Reason Song by Calum Scott - Ramadya Nesti, Nisha; Kusumawati, Paramita (Indonesian Journal Publisher, 2023)
This research aims to analyze the semantics meaning of You Are the Reason song by Calum Scott. The song tells of guilt and regret of past actions that he did to harm the lover, and he wishes to make it up by showing his eagerness and willingness to change for the better. The object of this study is to analyze the semantics meaning and to categorize the meaning into one of 7 types of semantics meaning. In theory, the researcher wishes to develop theoretical knowledge of literature and linguistics related to semantics and importance of songs. Practically, this research is useful as a reference for readers who will carry out similar research, especially in terms of linguistics and semantics, especially in songs lyrics. This research is included in the type of literary criticism, because the writer interprets and analyzes a literary work, especially songs. The data in this study were taken directly through lines of lyrics from the song, as well as from various other sources. The results of this study shows that the most dominant semantics type present in this song is the affected type, followed by conceptual type and the least is social type, which is non-existent in the song.